Case report of idiopathic thrombocytopenic purpura and tuberculosis in a 47-year-old male - Yudo Krisyulianto, Ignatius Loyola; Mulyono, Eddy (Institute of Computer Science (IOCS), 2024)
Idiopathic Thrombocytopenic Purpura (ITP) is a condition of low platelet count of unknown cause where most of the causes of ITP are the result of antibodies binding to platelets. One of the extra pulmonary manifestations of TB occurs in the hematological system which can cause anemia, leukopenia, leukocytosis, thrombocytopenia and thrombocytosis and ITP due to Tuberculosis (TB) is a rare manifestation of TB. This case report aims to describe a 47 year old male patient with ITP accompanied by TB. A 47 year old male patient came with complaints of weakness since 7 days ago. Based on the history, physical and supporting examinations carried out, the patient was diagnosed with ITP due to pulmonary TB. Manifestations of ITP due to TB are similar to ITP in general. Generalized purpura, bruising after minor trauma, epistaxis, subconjunctival hemorrhage and hematuria are possible manifestations. Treatment for ITP is to treat the underlying disease that causes it and specific treatment for ITP can also be given if the patient's platelets are very low. The specific treatment for ITP that can be given is corticosteroids or IVIG. Idiopathic Thrombocytopenic Purpura is a rare hematological manifestation of TB. Correct diagnosis and treatment play an important role in reducing the worsening prognosis of ITP patients due to TB.